Development of image processing software using visual basic 6.0 - Nurul Hakeem, Abd Rahim (2008)
Image processing is any form of information processing when both the input and output are images. The process does not reduce the amount of data present but rearranges it. Therefore, the development of image processing software is to enable image processing functions to be applied to input images to acquire an output images that has been processed using this software. The development of this software was done using Visual Basic 6.0 and includes basic image processing functions such as blurring and sharpening, edge detection and colour balancing. This software was designed to be user-friendly with a simple interface, yet able to perform basic image processing functions effectively. The input images also can be imported from attached webcam. Overall, this development of image processing software is to ensure image processing to be done using less memory space approximately 380KB compared to existing image processing software which may reach up to 1GB.